Use of a method of Pascal of calculation of checksums in noiseproof coding - Pevnev, Volodymyr; Tsuranov, Mikhail; Zemlianko, Heorhii; Kharchenko, Vyacheslav (Національний технічний університет "Харківський політехнічний інститут", 2019)
The subject matter of the article is opportunity use of a method of Pascal for finding of remainders of division of large numbers when using CRC. The goalis to analyze a possibility of use of a method of Pascal for definition of remainders of division in the CRC systems. Tasks: to analyze a possibility of use of CRC for noise-immune coding in different channels, to show a possibility of application of a method of Pascal for an image of noise-immune coding with use of checksums. The used methodsareanalytical method, methods of modal arithmetic’s. The received such results. The technique of calculation of Checksum of the message which are used for the control of integrity and restoration distorted the message is developed. Conclusions. Use of a method of Pascal for definition of remainders of division allows accelerating considerably process of search of various options the message, which will be restored. Realization of the offered method allows creating parallel structures, which give the chance to solve a problem of recovery of the message on the scale of real time.

Предметом вивчення в статті є можливість використання методу Паскаля для знаходження залишків від ділення великих чисел при використанні CRC. Метою є проаналізувати можливість використання методу Паскаля для визначення залишків від ділення у системах CRC. Завдання: проаналізувати можливість використання CRC для завадостійкого кодування у різних каналах зв’язку, показати можливість застосування методу Паскаля для способу завадостійкого кодування з використанням контрольних сум. Використовуваними методами є: аналітичний метод, методи модальної арифметики. Отримані такі результати. Розроблена методика підрахунку контрольної суми повідомлення, які використовуються для контролю цілісності та відновлення спотвореного повідомлення. Висновки. Використання методу Паскаля для визначення залишків від ділення дозволяє значно прискорити процес перебору різних варіантів повідомлення яке буде відновлено. Реалізація запропонованого методу дозволяє створити паралельні структури, які дають можливість вирішити задачу відновлення повідомлення в масштабі реального часу.
Використання методу Паскаля для підрахунку контрольних сум у завадостійкому кодуванні
Keywords: CRC; integrity; divisions behind a step; цілісність; ділення за модулем; залишки від ділення